DEVELOPMENT OF PHILOSOPHY AND SCIENCE, UNDERSTANDING THE PHILOSOPHY OF SCIENCE, AND DIRECTIONS OF THE PHILOSOPHY OF SCIENCE - Nabila, Nabila Muna Mufidah; Amril Mansur (Indonesian Journal of Islamic Studies (IJIS), 2025)
This article discusses the development of philosophy and science, and explains the meaning of philosophy of science and also the direction of development of philosophy of science itself. Philosophy of science is a branch of philosophy that discusses the foundations, methods and limitations of science, as well as the relationship between science and reality. As time progresses, science continues to develop rapidly, which then influences the direction of development of the philosophy of science itself. Basically, the philosophy of science only focuses on the question of what science is, and how science can be known correctly. However, as time goes by and there are many advances in the fields of science and technology, philosophy of science is now not only limited to basic theories, but also examines the ethical, social and technological aspects of science. The method used in this research is qualitative methods with the type of library research. Namely to find out how philosophy and science have developed, the meaning of philosophy of science, and how the philosophy of science is directed through books and reading literature related to this material.